Does Online Availability Increase Citations? Theory and Evidence from a Panel of Economics and Business Journals - McCabe, Mark J.; Snyder, Christopher M. (The Review of Economics and Statistics, 2015)
Does online availability boost citations? Using a panel of citations to economics and business journals, we show that the enormous effects found in previous studies were an artifact of their failure to control for article quality, disappearing once fixed effects are added as controls. The absence of aggregate effects masks heterogeneity across platforms: JSTOR has a uniquely large effect, boosting citations around 10%. We examine other sources of heterogeneity, including whether JSTOR disproportionately increases cites from developing countries or to “long-tail” articles. Our theoretical analysis informs the econometric specification and allows citation increases to be translated into welfare terms.